A cosmogenic 3He chronology of late Quaternary glacier fluctuations in North Island, New Zealand (39°S). (15th January 2016) - Eaves, Shaun R.; N. Mackintosh, Andrew; Winckler, Gisela; Schaefer, Joerg M.; Alloway, Brent V.; Townsend, Dougal B.
Abstract: Mountain glaciers advance and retreat primarily in response to changes in climate. Establishing the timing and magnitude of mountain glacier fluctuations from geological records can thus help to identify the drivers and mechanisms of past climate change. In this study, we use cosmogenic 3 He surface exposure dating and tephrochronology to constrain the timing of past glaciation on Tongariro massif in central North Island, New Zealand (39 ° S). Exposure ages from moraine boulders show that valley glaciation persisted between c. 30–18 ka, which coincides with the global Last Glacial Maximum. Reinterpretation of moraine tephrostratigraphy, using major element geochemistry analysis, shows that ice retreat and climatic amelioration at the last glacial termination was well underway prior to 14 ka. The equilibrium line altitude in central North Island, during the Last Glacial Maximum, was c. 1400–1550 m above sea level, which is c. 930–1080 m lower than present. Considering the uncertainties in the glacial reconstruction and temperature lapse rates, we estimate that this equilibrium line altitude lowering equates to a temperature depression of 5.6 ± 1.1 ° C, relative to present. Our mapping and surface exposure dating also show evidence for an earlier period of glaciation, of similar magnitude to the Last Glacial Maximum, which culminated prior to 57 ka, probably during Marine Isotope Stage 4. Good agreement between the timing and magnitude of glacier fluctuations in central North Island and the Southern Alps indicate a response to a common climatic forcing during the last glacial cycle. Highlights: A cosmogenic 3 He moraine chronology for the last glacial cycle. Moraines deposited in two events: 30–18 ka and prior to 57 ka. Moraine tephrostratigraphy indicates deglaciation prior to 14 ka. LGM snowline 930–1080 m lower than present. Snowline lowering suggests LGM 5.6 ± 1.1 ° C colder than present.